GULA KELAPA KRISTAL DAN POTENSI PEMANFAATANNYA PADA PRODUK MINUMAN - Ervina Mela; Nurul Fadhillah; Mustaufik Mustaufik (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2020)
Crystal coconut sugar is sugar that made from coconut sap which is processed to  powder or crystal. This sugar has lower Glycemic Index and higher levels of fiber and vitamin B12 than cane sugar. Other advantages are that it is more soluble, has longer shelf life, more attractive in shape, easier to package and transport, has a unique taste and aroma, and can be fortified with other ingredients. Crystal coconut sugar can be used as a substitute for sugar cane in various beverage products. This paper aims to provide an overview of the process, excellence, and potential use of crystal coconut sugar in beverage products sourced from research journals and scientific books. Crystal coconut sugar has the potential to substitute cane sugar in tamarind syrup products, traditional drinks, instant powder drinks, instant chocolate drinks, coffee mixes, and ice cream.